The smoker’s larynx: a histopathological study - Munjal, Manish; Garg, Bhavna; Munjal, Shubham; Saggar, Tulika; Garg, Avantika; ., Arshnoor; Mehta, Arnav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Larynx of chronic smokers was clinically evaluated under high powered magnification as well as on histopathology to study the effect of fumes of nicotine on the vocal cords. Methods: 32 chronic smokers undergoing Lewis suspension micro laryngeal surgery were selected from the laryngology clinics of Dayanand Medical College and Hospital, Ludhiana. Intraoperative findings were recorded and the specimens were sent for histopathological examination. The study was undertaken in a period of one and a half years (June 2009-December 2010). Results: Maximum patients 31% (10 patients) underwent microlaryngeal surgery were smokers in the middle age group (40-50 years) and minimum 9.3% (3 patients) were above 60 years of age. Vocal polyp/polypoidal change was seen in 7 (21.87%) patients was the predominant finding followed by a chronic hypertrophic change 5 (15.62%) patients. leucoplakia 4 (12.5%) cases, tubercular caseation 3 (9.3%), vocal nodules 4 (12.5%) and vocal cysts 1 (3.125%) were the other findings in our series. Conclusions: Nicotine fumes affect the epithelium of the vocal cord leading to hypertrophic or hyperplastic transition. Vocal cord polypoidal change, squamous cell carcinoma and chronic hypertrophic laryngitis, in that order were the lesion in our series.